O drama como método de ensino de comportamentos autoprotetivos para prevenção de violência sexual infanto-juvenil - Rossi, Luiza Lemos de (2024)
This dissertation investigates elements of Drama as a teaching method (Cabral; Vidor) applied to the development of a repertoire of self-protective behaviors in children, based on the 3 R's: Recognize, Resist, Report (Soma; Williams; Wurtele). For data production, two Drama Workshops were conducted for teachers of the Early Years of Elementary School: one group linked to the public network and another to the private network, located in the municipality of Santa Maria, RS. In the Workshops, a formative, sensitive, dialogical, interdisciplinary, and creative activity was promoted, reviewing concepts related to the prevention of child sexual abuse and violence (Sanderson; Rodrigues), as well as Education in Sexuality. Under the lens of Performative Pedagogy (Hartmann; Pereira; Pineau; Schechner; Icle; Bonatto) and based on the analysis of seven dramatic focuses created by the participating teachers, reflections were made on theoretical-methodological resources to discuss themes such as bodily autonomy, healthy socio-affective relationships, and non-violent sexualities from primary school.